(untitled) (Archives of Mechanics - Test, 1998)
The dissipative motion of quantized vortex line, after reconnection, is studied within the localized induction approximation. The numerical simulations of vortex line evolution help to determine the rate of the line-length changes. In the absence of counterfiow, the vortex line shortens after each reconnection and line-length reduction is calculated as a function of friction parameter a and reconnection angle φ. The obtained results sugest that the decay of quantized vortex tangle is due to line-length reduction which occurs after each reconnection of vortex lines. In the presence of the counterflow, however, the reconnection may initiate a generation of a cascade of vortex loops. These loops blow up, so the total length of vortices grows up and the quantum turbulence can be generated.